Taxonomic and functional shifts in soil nematode communities following estuarine island reclamation - Pan, Sufeng; Liang, Jing; Wu, Haibing; Cai, Yongli (Frontiers in Ecology and Evolution, 2025)
Coastal land reclamation dramatically alters ecosystem structure and trajectories of ecological succession, yet knowledge about soil faunal colonization and community assembly in reclaimed coastal land is scarce. In this study, we investigated taxonomic and functional shifts in soil nematode communities following reclamation in sites at Hengsha Island, China. Six reclamation stages were identified based on reclamation age and vegetation type, including tidal flat, 1-year bare field, 3-year halotolerant pioneer community, 5-year grassland, 10-year, and 50-year secondary forests. We collected data on the morphological and life history traits of soil nematodes, including body size, cephalic setae, amphids, tail shape, life history strategy, and feeding habit, to assess the functional responses of nematodes to different reclamation stages. We found a significant decrease in both taxonomic and functional diversity as tidal flats were converted to dry land, followed by a gradual recovery that progressed with increasing reclamation age. Significant shifts in the taxonomic and functional composition of soil nematode communities were also observed. Tidal flat reclamation decreased the relative abundance of marine nematodes with cephalic setae, large amphids and clavate/conicocylindrical tails. With increasing reclamation age, bacterivores and r-strategists with conical and long tails were displaced by fungivores, herbivores, and K-strategists with rounded tails. These shifts were driven by changes in soil water content, organic matter, plant communities, and stress factors, such as pH and salinity. Our findings highlight the critical role of morphological and life history traits in understanding how soil nematode communities adapt to human-induced environmental changes, providing valuable insight into the long-term ecological impacts of coastal reclamation on soil biodiversity.